Multiple accessing, multi-numerology, hybrid waveforms - Şahin, Mehmet Mert; Arslan, Hüseyin (Wiley, 2021)
This chapter focuses on the issue of how to intelligently share the resources in a hyperspace whose dimensions are time, frequency, space, beam, and code. Most of the wireless communication standards prefer to design orthogonal frames in order to manage the interference between the users. The concept of non-orthogonal multiple access has been proposed to overcome the limitation of orthogonal resources. The chapter also provides a comparison between random access schemes. It presents insight into which specific scheduled or random access technique to apply. The chapter emphasizes the real wireless system development problem of how to design a multiuser system depending on the system requirements, traffic characteristics of users in the network, performance measurements, channel characteristics, and other interfering systems operating in the same bandwidth. It examines a novel concept called radar-sensing and communication convergence by the perspective of the hybrid waveforms concept.
Keywords: Hybrid Waveforms; Non-Orthogonal Multiple Access; Orthogonal Frames; Random Access Schemes; Wireless Communication; Wireless System Development